The Concept of Hulul: Al-Hallaj's Thought and Its Relevance in Sufism - Yogi Fery Hidayat (Journal of Noesantara Islamic Studies, 2024)
This study discusses the concept of Hulul in the thought of Abu Mansur al-Hallaj, a controversial 9th-century Sufi who introduced the idea of spiritual union between God and man. Hulul refers to the belief that in mystical experience, a Sufi can attain a spiritual union with God, as reflected in al-Hallaj's famous statement, Ana al-Haqq (I am the Truth). This research uses a qualitative approach with literature review, as well as historical, philosophical, and theological methodologies to examine the doctrine of Hulul and its impact on the Sufi tradition. The analysis also addresses the relevance of al-Hallaj's thought to later Sufis, such as Jalaluddin Rumi and Ibn Arabi, who in various ways developed the idea of the union between man and God. The findings indicate that, despite Hulul facing significant criticism from orthodox scholars for being seen as contradictory to tauhid (the concept of God's oneness), this teaching still had a substantial influence on the development of Islamic mysticism and Sufism. The concept of Hulul remains one of the primary symbols of profound mystical experiences within the Sufi tradition.